Heterogeneous Cytoskeletal Force Distribution Delineates the Onset Ca2+ Influx Under Fluid Shear Stress in Astrocytes - Maneshi, Mohammad M.; Sachs, Frederick; Hua, Susan Z. (Frontiers in Cellular Neuroscience, 2018)
Mechanical perturbations increase intracellular Ca2+ in cells, but the coupling of mechanical forces to the Ca2+ influx is not well understood. We used a microfluidic chamber driven with a high-speed pressure servo to generate defined fluid shear stress to cultured astrocytes, and simultaneously measured cytoskeletal forces using a force sensitive actinin optical sensor and intracellular Ca2+. Fluid shear generated non-uniform forces in actinin that critically depended on the stimulus rise time emphasizing the presence of viscoelasticity in the activating sequence. A short (ms) shear pulse with fast rise time (2 ms) produced an immediate increase in actinin tension at the upstream end of the cell with minimal changes at the downstream end. The onset of Ca2+ rise began at highly strained areas. In contrast to stimulus steps, slow ramp stimuli produced uniform forces throughout the cells and only a small Ca2+ response. The heterogeneity of force distribution is exaggerated in cells having fewer stress fibers and lower pre-tension in actinin. Disruption of cytoskeleton with cytochalasin-D eliminated force gradients, and in those cells Ca2+ elevation started from the soma. Thus, Ca2+ influx with a mechanical stimulus depends on local stress within the cell and that is time dependent due to viscoelastic mechanics.